Performance of Wheat Genotypes Under Different Dates of Sowing in Southern Part of Kailali District, Nepal (American Journal of Life Science and Innovation, 2022)
An experiment was conducted in the Kailali district to study the performance of wheat genotypes under different sowing from December, 2017 to April, 2018. The field experiment was conducted in Randomized Complete Block Design with a total of 18 treatments consisting of 2 dates of sowing (November 4 and November 20 ) and 9 wheat genotypes(WH1105, HD2733, HD2824, HD2967, Borlaug100, HD3086, PBW550, NL971 and PBW373). Grain yield  (5.802 ton/ha),spike length(17.94 cm) and biomass yield(13.16 ton/ha) of NL 971 was highest. HD 2733 had highest number of effective tillers (519.1/ m2) while number of grains per spike(59.80) was highest in HD 2967. PBW 373 had lowest grain yield (4.551 ton/ha), Borlaug 100 was the variety with minimum number of tillers per m2 area (401.3), minimum spike length(15.14 cm)  was observed in HD 2733 ,HD 3086 had lowest no. of grains per spike(42.12). Grain yield(5.328 ton/ha) , effective tillers per m2(475.5) , spike length(16.95 cm), number of grains per spike (53.12), biomass yield(11.45 ton/ha)    was recorded maximum in wheat sown on 20th Nov. Grain yield (4.893 ton/ha),effective tillers(435.1), spike length(15.66 cm), grains per spike(49.59) and biomass yield(10.49 ton/ha) was recorded minimum in wheat  sown on 4th Nov. Maximum test wt. (50.83 g ) was found in HD 2733  of 20th Nov. and the lowest test wt. (40.47 g) was found in PBW 550 of 20th Nov.